Experimental Characterization of a Compact Milli-Channel Heat Exchanger for Liquid–Liquid Heat Transfer. Issue 22 (15th December 2020) - Portha, Jean-François; Henry, Guillaume; Père-Gigante, Alexandra; Commenge, Jean-Marc
Abstract: The use of Milli-Channel Heat Exchangers (MCHE) presents numerous assets: efficient heat transfer, huge compactness, and limited pressure drop. For an engineer, the Fanning friction factor and the convective heat transfer coefficient are two main parameters to describe the performance of a heat exchanger. A brazed MCHE with rectangular channels in stainless steel made by the Institut für Mikrotechnik Mainz (IMM, Mainz, Germany) has been characterized experimentally and theoretically in a counter-current configuration. The selected working fluids are deionized water and oil without any phase change during experiments. The pilot unit ensures measurements of pressure drops, temperatures, and volumetric flow rate of each fluid flowing in laminar regime. A one-dimensional model has been developed. The temperature and pressure profiles of each fluid are represented by differential equations associated with boundary conditions. The system of coupled equations consists in a two-point boundary value problem solved numerically by the Matlab software. The parameters of a Nusselt number correlation are identified together with those of a Fanning friction factor one by minimizing a sum of squared differences between experimental and predicted data. The calculated temperature and pressure profiles present a good agreement with measurements. A statistical analysis shows that each optimized parameter is significant.